Pengembangan E-LKPD Berbasis Predict-Observe-Explain (POE) Menggunakan Liveworksheets pada Materi Kesetimbangan Ion dan pH Larutan Penyangga - Sarmila Eka Putri; Abdullah Abdullah; Sri Wilda Albeta (Hydrogen: Jurnal Kependidikan Kimia, 2022)
This research was conducted at the Chemical Education Study Program, Faculty of Teacher Training and Education (FKIP) Riau University, Pekanbaru in the even semester of 2021/2022 with trials conducted at SMAN 3 Tualang and SMAN 6 Pekanbaru. This study aims to produce POE-based E-LKPD using Liveworksheets on the subject of ionic solutions and pH of buffer solutions. Using the Plomp development model, this study was planned as part of the R&D process. Validation sheet and user feedback survey used for data collection. Validation was carried out by four independent validators, showing the percentage of valid categories of 98.21%, 100%, 96.87%, 95.83%, and 93.05% for incorrect, POE model features, language, presentation, and visuals. 3 students participated in an individual trial, in which data on the amount of time and scores obtained from using the E-LKPD, as well as students' ideas and feedback, were collected. The average percentage of teacher evaluation of E-LKPD is 93.98%, and the percentage of student evaluation is 89.34%; This finding shows that the E-LKPD created is in accordance with the education setting.